The correlation between blended learning motivation with knowledge and learning satisfaction among nursing students - Fini Alfiani Cantigi Ram; Sri Suparti; Kala Raani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Blended learning is a new system that combines face-to-face and online learning. This new system in the Muhammadiyah Purwokerto University (UMP) requires evaluations from the students’ feedback. Students' motivation was the influential factor on both accomplishments and presences in online learning. Students’ motivation, satisfaction, and knowledge of blended learning were the components for the effectiveness of the course.Objective: The study aims to describe the level of motivation, knowledge, and learning satisfaction, and also to observe the correlation of motivation on blended learning with knowledge and learning satisfaction.Methods: This quantitative research used a cross-sectional approach. Data collection techniques used were questionnaires in the google form. The researcher made the questionnaire and has been tested for validity on 30 respondents with r-value of >0.3 (Pearson product-moment). Cronbach alpha for the reliability was ranged from 0.750 to 0.828, so it is valid and reliable to use. The sample was 254 nursing students from the 3rd, 5th, and 7th semesters selected by quota sampling. Data were analyzed by Pearson product-moment correlation.Results: The results showed that students obtained moderate motivation (71.3%), knowledge (81.5%), and satisfaction (70.5%). There was a significant correlation between motivation with knowledge (r=0.650, p<0.01) and learning satisfaction (r=0.636, p<0.01) on blended learning.Conclusion: The blended learning method can be used as a teaching and learning method for future nursing education, followed by evaluation. Furthermore, the lecturer should consider the students’ characteristics and expectations toward blended learning.